Study on SNCR Denitration of W-flame Boiler and Its Effect on the Flow Field of SCR Inlet Section - Haijie CHEN; Wu MA; Gongyi LIU; Pan GAO (Zhongguo dianli)
Because of the high NOx concentration of W-flame boiler, the coupling denitrification technology consisting of low nitrogen combustion, SNCR and SCR has been applied by several power plants. However, severe violations of the ammonia escape concentration of SCR have taken place in the actual operation since the coupling denitrification technology was carried out. In this paper the effects of boiler load, flow field of urea spray section and ammonia-nitrogen molar ratio on the SNCR denitrification and inlet flow field distribution of SCR were studied for a 600 MW W-flame boiler by numerical simulation and experimental verification. It is found that the non-uniform arrangement of SOFA along the front and rear walls of the boiler is the major cause for the unevenly distributed velocity and temperature fields of urea spray layer. With the decrease of boiler load, the average temperature of reducing agent spray section tends to be close to the optimum denitrification temperature, and the NOx removal rate increases gradually. The temperature, velocity and NOx concentration at the inlet section of SCR is not uniformly distributed. Specifically, with the increase of SNCR denitrification rate, the unevenness of NOx concentration distribution at SCR inlet section intensifies such that the relative standard deviation of NOx may reach 35%~53% at different boiler loads. Moreover, the usage of SNCR has significant impacts on the NOx distribution across the SCR inlet section, which may eventually lead to the serious violation of the concentration of ammonia escaping from SCR. To solve this problem, it is suggested to optimize the SOFA arrangement and install new type of gas mixer at the entrance section of SCR.